Anaesthesia in patients with severe obesity: An uncharted journey - Nitin Kapoor; Mouleeswaran Sundaram; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Administration of anaesthesia to patients with severe obesity comes with its own challenges. This has become even more relevant in current day times as the number of people with severe obesity is increasing rapidly. There is a need for all treating doctors, including the referring physician, the anaesthetist, the operating surgeon, and the post-operative intensivist, to understand and counsel about these risks to patients with obesity in the perioperative period. In this paper, the authors highlight the risks associated with anaesthesia in a patient with severe obesity. In addition, the risk assessment and the impact of obesity on the usage of different anaesthetic agents are also highlighted. Keywords: Anesthesia & Obesity; Obesity Surgery Mortality Risk Score (OSMRS); Bariatric surgery; Obesityrelated perioperative mortality.